Spremembe fizikalnih lastnosti hrastovega lesa iz zgodovinskih konstrukcij v življenjski dobi - Straže, Aleš (Les (Ljubljana), 2018)
We examined the physical properties of oak wood (Quercus sp.) felled four to 512 years ago, grouped in age groups of 100-600 years. The wood originated from recently felled trees and from historical constructions in Slovenia. The selected wood was dendrochronologically dated. We made standardized samples and determined wood density, colour, dimensional stability and sorption properties. Visual and CIELab analyses showed that the colour of the heartwood became darker with age. Historical oak wood was characterised by lower hygroscopicity and higher dimensional stability, especially in the tangential direction, as well as reduced transverse shrinkage anisotropy compared to recently felled wood. The density of oak wood did not change with age, it was dependent on tree-ring widths and the proportion of latewood, and increased along with the proportion of latewood. Besides ageing, the location of wood during its service life and exposure to climate fluctuations also seemed to influence the dimensional stability and hygroscopicity of historical oak.
Keywords: ageing; barva; colour; Croatian Growth; dimensional stability; dimenzijska stabilnost; hrast; hygroscopicity; les; lesena gradnja; oak; Quercus sp.; sorpcija; sorption; staranje; wood